PERAN MEDIA SOSIAL SEBAGAI MEDIA SARANA INFORMASI POLITIK - Sintyananda Gayatri; Ida Bagus Canirartha Satwika (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The development of communication technology in the digital age has shifted the role of conventional media. Social media plays a role in the dissemination of information to the wider community in all fields, one of which is in the field of politics. The choice of using social media to build a strong political communication network is natural in an effort to gain support. Therefore, researchers are interested in conducting research related to the role of social media as a means of political information. Based on the background above, the research problem that can be formulated is: How is the role of social media as a means of political information. The purpose of this study is to elaborate and provide an overview of the role of social media as a means of political information. The survey was conducted for 24 hours on April 18-19, 2022 using the Google Form application that managed to collect data from 140 community respondents domiciled in Denpasar City. Data analysis is done descriptively by and looking at the percentage / proportion of respondents who answered on the choice of answers on the questionnaire. The study found that 92 respondents (65.7%) agreed that social media plays a role in helping to get political information. This was supported by 113 respondents (80.7%) who used the internet / social media in seeking political-related information. Of these, 83 respondents (59.3%) said they often access political information on social media. Fifty-eight (41.4%) chose Instagram for political information. More widely accessed political information is information on political issues (103 respondents (73.6%)). But 99 respondents (70.7%) said political information on social media was hesitant to be believed. So many as 67 people (47.9%) respondents said they were rarely provoked by political news on social media. Keywords: The Role of Media, Social Media and Political Information.